Wiktor Steffen i jego Słownik warmiński - Sobolewska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
The paper presents Słownik warmiński of Wiktor Steffen as an unique work of the Polish dialect lexicography. It shows also the figures of the author and his brother Augustyn who rendered great service in research of the culture of Warmia. It discusses the editorial principles of the dictionary and its rich content. It relates to the charges of the first critics of the vocabulary. The paper treats Słownik warmiński as a personal, subjective work strongly influenced by the biography of the author – autochthon. It presents the different ways of use the content in the dialectological studies on multi-volume Słownik gwar Ostródzkiego, Warmii i Mazur conducting in the Institute of the Polish Language in the Polish Academy of Science (IJP PAN).